Analisis Tebal Lapisan Perkerasan Lentur Menggunakan Metode Manual Desain Perkerasan 2017 Pada Jalan Lingkar Sebatik Perbatasan Indonesia-Malaysia - Andria Imran; Misdar Alamsyah; Yoseph Yoseph; Syarifudin Syarifudin (Jurnal Impresi Indonesia, 2025)
This study aims to analyze the thickness of the bending pavement layer on the Sebatik Ring Road, Indonesia-Malaysia border, using the 2017 Pavement Design Manual method. The road has a strategic role as the main connecting infrastructure in border areas facing geographical challenges, such as diverse soil types, as well as tropical climates with high rainfall and significant air humidity. This condition affects the durability and performance of the pavement, so optimal design is needed to ensure the durability of the road against traffic loads as well as local environmental conditions. This study uses primary data in the form of a test of the mechanical properties of the basic soil and secondary data in the form of traffic volume and environmental conditions. The analysis was carried out based on a mechanistic-empirical approach in accordance with the 2017 Pavement Design Manual, including the determination of the thickness of the surface layer, upper foundation, and lower foundation. The results of the study are expected to provide recommendations for pavement designs that are able to withstand traffic burdens and climate challenges in Sebatik. In addition, this research provides practical benefits for infrastructure development in border areas and supports better connectivity. These findings can also be used as a reference in road infrastructure planning in areas with similar geographical and climatic conditions, both in Indonesia and other tropical regions.